The Impact of Clinical Atropine Use in Taiwanese Schoolchildren: Changes in Physiological Characteristics and Visual Functions - Hui-Ying Kuo; Ching-Hsiu Ke; Shyan-Tarng Chen; Han-Yin Sun (MDPI AG, 2021)
Taiwan is commonly noted for its high prevalence of myopia, as well as a long history of more than 20 years of using atropine to control myopia. However, the clinical implications are rarely discussed. This is a cross-sectional study investigating the influence of topical atropine instillation on ocular physiology, visual function, and visual discomfort in children. Aged 7 to 12 years, 212 schoolchildren were recruited and divided into the atropine group and the non-atropine group. Physiological characteristics such as pupil size and intraocular pressure were measured, and a variety of visual functions was also evaluated. A questionnaire was used to investigate the side effects and visual complaints caused by atropine treatment. There was a significant difference in pupil size (OD: 5.40 ± 0.90 vs. 6.60 ± 1.01 mm; OS: 5.42 ± 0.87 vs. 6.64 ± 1.00 mm, p < 0.001) between the two groups. Reductions in near visual acuity, accommodation, convergence ability, and stereopsis were observed in the atropine group. The horizontal pupil diameter enlarged, and visual functions were greatly affected after administration of topical atropine. The changes in visual function during atropine therapy need to be carefully monitored by clinicians, while patient compliance is usually the key to success.